Reflecting on Mortality: Grave Visiting in Light of the Quran and Hadith - Dr. Faiza Qayyum; Dr. Abbas Ali Qayyum (Karachi Islamicus, 2023)
Graves as well as death have been surrounded by mystery before and after the introduction of Islam. One of the oldest graves are located in Palestine and the tradition of burying the deceased has continued through the time. However, there is still a controversy on-going about visiting graves, especially in the Muslim societies. In the early ages of Islam, visiting graves were prohibited but later on permitted as it reminds the people about the death, life hereafter and soften the hearts. Many passages in the Quran and several hadiths from Sahih Bukhari and Sahih Muslim encourage people to remember the death, the deceased and the life hereafter. The main purpose of people remembering the death and the life after death is to change people’s behaviour for the better. In this comprehensive review, we evaluate the legitimacy of visiting graveyards based on references from Quran and the two books of hadiths, Sahih Bukhari and Sahih Muslim.